Systems Education for a Sustainable Planet - Robert Y. Cavana (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The issues facing humanity have become increasingly complex due to the fact they are embedded in a global web of ecological, economic, social, cultural and political processes that are dynamically interlinked. The capacity to conceptualise and redesign solutions, in systems and sustainability terms, will increasingly be what society and employers expect. This "expectation" is globally one of the biggest challenges for education. This Special Issue highlights key developments in the area of systems education and how some of the many challenges are currently being addressed. The 15 articles published fall into five groups: how to design learning systems for systems thinking and sustainability education; insights from the various systems education programs available internationally; different approaches to teaching systems thinking and sustainability; how systems education can be tailored to broaden systems education beyond universities; and possible future pathways for systems education for a sustainable planet. The range and magnitude of the contributions to this book illustrate the diversity of systems education practices and programs (learning systems) in the global systems community, and the relevance of systems thinking and practice to examining issues crucial to the long-term sustainability of the planet.